Multi-factor Deformation Analysis for Newly-built Tunnel Obliquely Under-passing Existing Tunnels by Small Clearance - ZHAO Yao; HUANG Changxin; ZHANG Qing; SHAO Jingqi; GAO Ziming; ZHANG Lianzhen; CHEN Jian; WANG Chong; YU Lei (Chengshi guidao jiaotong yanjiu)
［Objective］ In construction scenarios involving new tunnel construction under-passing existing tunnels by extremely small clearance, the new tunnels are highly susceptible to deformation, collapse, and other safety risks, thereby threatening the normal operation of existing lines. Therefore, it is necessary to analyze the factors influencing deformation when new tunnels obliquely under-pass existing tunnels by small clear distances. ［Method］ Based on the actual construction case of Qingdao North Station-Cangkou Station interval on Qingdao Metro Line 8, where the tunnel obliquely passes under the existing operating tunnel on Line 3, the finite element calculation software ABAQUS is employed to numerically simulate the excavation process. The impact of three key factors on the deformation characteristics of the existing tunnel are examined in-depth, including excavation method, excavation step length, and surrounding rock conditions. ［Result & Conclusion］ Compared to the full-face excavation method, the bench excavation method would increase the maximum vertical displacement and horizontal displacement of existing tunnel by 24%, indicating that the full-face method performs better in controlling tunnel deformation. Meanwhile, the increased excavation step length and deteriorated surrounding rock conditions significantly exacerbate the displacement of the existing tunnels. When the step length increases from 0.5 m to 1.5 m, the vertical displacement will increase by 13% and the horizontal displacement by 28%, attributed to crossing geometry, stress release, redistribution, and deformation constraints. When the surrounding rock grade deteriorates from Grade III to Grade V, the vertical displacement will surge by 302% and horizontal displacement by 205%, causing an influence far exceeding that of the excavation method and step length. In the excavation mileage-displacement curve, the excavation method determines the curve shape, while step length and surrounding rock conditions dictate the displacement magnitude. For small-clearance oblique under-passing projects, it is recommended to prioritize the full-face excavation method and small step lengths under favorable surrounding rock conditions, so as to mitigate the stress and deformation in the existing tunnel.